Research trends on neutrophil extracellular traps in ischemic stroke: a scientific metrology study - Xu, Yaji; Gong, Xingyu; Wang, Yilin; Liu, Xinyu; Pu, Haomou; Jiang, Hongjie; Yu, Xiaoping (Frontiers in Pharmacology, 2025)
BackgroundIschemic stroke (IS) remains a leading global cause of mortality and chronic disability. Neutrophil extracellular traps (NETs), recently identified as neutrophil-derived structures that trap and neutralize pathogens, have increasingly drawn attention for their involvement in IS pathogenesis. Despite a surge in related research, no bibliometric analyses have yet examined the knowledge framework and trends within this emerging field. Here, we conducted a systematic bibliometric analysis to map the research landscape and identify current and potential hotspots regarding NETs in IS.MethodsRelevant literature published between 2014 and 2024 was systematically retrieved from the Web of Science Core Collection (WoSCC) database. Multiple analytical tools, including CiteSpace, VOSviewer, R package “bibliometrix,” and Python scripts, were employed to explore publication trends, academic collaborations, prominent research themes, and emerging topics.ResultsNinety-two publications were eligible for bibliometric assessment, supplemented by an additional latent Dirichlet allocation (LDA)-based topic analysis of 4,504 documents. China (30 publications) and the United States (23 publications) emerged as leading countries in terms of research output, with global collaboration networks predominantly centering around the United States. Noteworthy contributions also arose from European institutions, particularly Katholieke Universiteit Leuven and Karolinska Institutet. The leading authors identified were Desilles, Jean-Philippe, Ho-Tin-Noé, Benoit, and Mazighi, Mikael. Journals such as Stroke, Annals of Neurology, and Nature Communications significantly influenced this domain. Three main research hotspots emerged: (1) “promoting effect of protein arginine deiminase 4 (PAD4) in NET formation,” (2) “cell-free DNA as a biomarker for disease diagnosis,” and (3) “influence of platelets and thrombosis on NETs-related diseases.”ConclusionOur study offers an extensive overview of existing literature and evolving research trajectories concerning NETs in IS, providing researchers with clear insights into current trends and future investigative directions. Nevertheless, our study has limitations—including dependence on a single database (WoSCC), restriction to English-language publications, and inherent constraints of the LDA methodology—that merit consideration in interpreting these findings.